The Context of Niklas Luhmann’s Theory - Mickūnas, Algis (Sociologija. Mintis ir veiksmas, 2003)
More recent continental thought is developing a social theory based on phenomenological concepts of human action and experience. At the base of this theory there is the reevaluation of the concept of time and the function of science and theoretical thought. It attempts to escape the assumption that theories and theoreticians have an extra-temporal and extra-social vantage point unaffected by social change, conditions, historical period , modes of perception and valuative interests. Theoretical and scientific thought is inner-worldly, inner-social and hence temporal and must be understood in terms of human action within society and history. Furthermore, a question of the last interpreter and the subject of selectivity must be raised. How are we to conceive of the subject who interprets, selects and correlates social actions and phenomena? It too must be understood in inner-social, temporal terms. To better understand this theory it is necessary to sketch the series of problems which led to its formulation. Although there are many writers who have contributed to the development of the contemporary continental social thought, only the topics relevant for the framing of Luhmann’s thinking will be introduced.